Towards a Global Englishes-aware National English Curriculum of China. (14th August 2021) - Liu, Haibo; Fang, Fan
Abstract: Although researchers and practitioners have discussed the concept of Global Englishes (GE), the degree of GE's influence in the practical use of English is much wider and deeper in the real world than in the field of education. Mainstream ELT practices tend to adhere to native and fixed norms, which are regarded as the central problems in ELT from the perspective of the GE paradigm. Although a GE-oriented pedagogy has been discussed, studies on curriculum in the Chinese ELT context from the GE perspective are relatively rare. This paper aims to investigate the extent to which the National English Curriculum (NEC) in China reflects GE-oriented phonology and cultural learning. The study adopted a content analysis in which the NEC statements on phonology and cultural aspects were identified and discussed. After reporting the findings, the paper further discusses some pedagogic implications about curriculum and language teaching from the GE perspective.